The waterproofing process of reinforced concrete flat roof on terrace house at Teluk Intan, Perak / Nur Farah Aina Hairul Anuar - Hairul Anuar, Nur Farah Aina (Universiti Teknologi MARA UiTM,Perak, 2022)
Department Of Built Environment And Technology Perak Branch Seri Iskandar Campus Universiti Teknologi Mara (UiTM) has enlisted the subject Industrial Training (BSR669) in its course outline which will provide pre-professional work experience to all the students taking the subject. The subject requires the students to undergo the training at selected organization and the industrial training period is four months. Furthermore, during the industrial training, students are encouraged to contribute to the organization by joining activities and carryout the responsibilities given to them professionally. Industrial training is relevant since the students are able to show their skills and prepare for the real working environment in the near future.